Malaysian Consumer Behaviour towards Internet Banking: An Application of Technology Acceptance Model - Othman, Bestoon; Harun, Amran; Answer Ismail, Darbaz; Majed Sadq, Zana; Ali, Sher; Stephen Ramsey, Thomas (International Journal of Psychosocial Rehabilitation, 2019)
The Technology Acceptance Model (TAM) explains customer behaviour towards using internet banking for fastest services. On the other hand, slow adoption of internet banking is depriving customers of this new technology. This research is based on the quantitative approach with 375 questionnaires collected from the faculty and students of the University Technology Malaysia. This study examined the technology acceptance model, which comprises individual perceived usefulness (PU), perceived ease of use (PEU), and perceived credibility (PC) on behavioural intention to use internet banking. The outcome shows all the variables have positive effects on the use of internet banking in daily life. This has highlighted the importance of the TAM model in understanding how Internet banking helps the banks in reducing time and resources for consumers.